Potentials of binderless boards production for sustainable building development in nigeria: a review (2023)
Nigeria, a developing nation with a population of about 200 million people, is currently experiencing a national housing deficit of approximately 17 million units. With an expected annual national population growth rate of about 3% and an annual urban population growth rate of about 4%, Nigeria's population is becoming more and more concentrated in metropolitan regions, towns, and cities where housing deficits are more pronounced. The high cost of construction materials contributes majorly to Nigeria's housing problems, prompting several researches into the use of local materials as alternative building materials. In Nigeria, lignocellulosic biomass resources such as forestry residues, agricultural wastes, and industrial remnants are available in large quantities and are being investigated for use in the production of wood-based panel boards. However, the formaldehyde-based adhesives used in their manufacture emit emissions that pollute the environment and harm human health. The goal is to create cheap, environmentally friendly binder-less boards from waste lignocellulosic materials. In pursuit of a sustainable built environment in Nigeria, this review investigates the potentials of binder-less board production from lignocellulosic biomass.